2017
DOI: 10.1016/j.apgeochem.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements sorption to iron oxyhydroxide: Model development and application to groundwater

Abstract: Iron oxyhydroxides are among the most important colloids that control rare earth elements (REE) concentrations and transport in natural hydrosystems. In this study, REE surface complexation to iron oxyhydroxides (Fe(OH) 3 (a)) was described by using the Donnan diffuse layer model and a two-site (i.e. ≡Fe s OH and ≡Fe w OH) model. The specific surface area and pH of zero charge were fixed as 100000 m 2 /mol and 8.0, respectively. The surface site density for weak and strong binding sites were fixed at 0.1 mol/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 56 publications
4
55
0
3
Order By: Relevance
“…In this study, the formation of iron (III) minerals on the rice root was observed both in the presence of Fe(II) chloride or Fe(II) sulfate. (Liu et al, 2017). This suggests that as the radii of the REE decreases the stronger the binding to HFO as shown in Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 68%
See 4 more Smart Citations
“…In this study, the formation of iron (III) minerals on the rice root was observed both in the presence of Fe(II) chloride or Fe(II) sulfate. (Liu et al, 2017). This suggests that as the radii of the REE decreases the stronger the binding to HFO as shown in Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 68%
“…5c and 5d for the quantification of REE in concentrations in roots, show a decrease in MREE and HREE concentrations, both in the presence of Fe(II) sulfate and Fe(II) chloride and at 0.5 mg/L and 1 mg/L REE. This result suggests the presence of Fe (III) plaques on the rice root, as log 10 K values propose a stronger binding of the MREE and HREE to hydrous ferric oxide strong sites (Liu et al 2017). In addition, the "flat" patterns observed for the REE series in Fig.…”
Section: -mentioning
confidence: 71%
See 3 more Smart Citations